Oligomerization of Carbon Monoxide in Plasma of the Dielectric Barrier Discharge; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Litvishko E. S. Evgeniy Sergeevich (Discharge and Plasma-Beam Technology, 2016)
Title screen